Preparation method and application of shape-controllable high-performance carbon wave-absorbing material
Through hydrogen bond self-assembly and heat treatment technology, high-performance carbon absorbing materials with controllable morphology were prepared, which solved the problems of impedance matching and limited absorption frequency band of existing carbon absorbers, and achieved efficient electromagnetic wave absorption performance in a wide frequency range .
Patent Information
- Application Number
- CN202411766627.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-04
AI Technical Summary
There is an imbalance between the impedance matching characteristics and attenuation characteristics of existing pure carbon absorbers, and the effective absorption frequency band is limited.
The morphology of the hydrogen bonded organic frame is regulated by hydrogen bonding between melamine and cyanuric acid, and the porous hollow structure and short-range ordered carbon nanocrystals are formed through heat treatment to prepare a one-dimensional one High-performance carbon absorbing materials in tubular and three-dimensional mesh.
The impedance matching characteristics and electromagnetic wave absorption performance have been improved. The minimum reflection loss of the material reaches -55.32dB and -26.49dB. The effective absorption bandwidth covers the frequency range of 2-18GHz, meeting the application requirements of "thin, light, wide and strong".
Smart Images

Figure CN119430146A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of absorbing materials, and in particular relates to a preparation method and application of a high-performance carbon absorbing material with controllable morphology. Background Art
[0002] Microwave technology represented by 5G has developed rapidly and is widely used in many fields such as national defense, military, electronic communications, and medical treatment. The thermal and non-thermal effects and long-term cumulative effects of electromagnetic waves pose a serious threat to human health, the operation of precision equipment, and even national security and information protection. Therefore, it is urgent to design and develop thin and efficient electromagnetic wave absorbing materials to meet these challenges.
[0003] Carbon materials are excellent wave absorbing materials due to their low density, high adjustability, good chemical stability and diverse preparation methods. However, due to the intrinsic high conductivity and simple structure and morphology of common carbon materials, such as carbon black, graphite and graphene, it is difficult to achieve a balance between impedance matching characteristics and attenuation characteristics. Due to the skin effect, incident electromagnetic waves are easily reflected back to free space on the surface of these materials, so it is difficult for them to achieve efficient wave absorption in a wide frequency range. In order to solve the above problems, some researchers have constructed carbon-based absorbers with different morphologies by means of template method to reduce the wave impedance of the absorber body, such as one-dimensional carbon nanotubes, two-dimensional carbon nanosheets and three-dimensional porous carbon. However, the electromagnetic loss introduced by a single shape geometric effect is still very limited and is not enough to significantly broaden the absorption bandwidth of carbon-based absorbers. At the same time, the template addition and removal involved in the template method is not conducive to the simplification of the preparation process and the control of manufacturing costs, limiting the practical application potential of these absorbers. Summary of the invention
[0004] The purpose of the present invention is to solve the technical problems of the imbalance between the impedance matching characteristics and the attenuation characteristics of the existing pure carbon absorber and the limited effective absorption band, and to provide a preparation method and application of a high-performance carbon absorbing material with controllable morphology.
[0005] One of the purposes of the present invention is to provide a method for preparing a high-performance carbon absorbing material with controllable morphology, the method being carried out according to the following steps:
[0006] S1: Under heating conditions, melamine and cyanuric acid are dissolved in deionized water or ethanol aqueous solution respectively, and then the melamine solution is added dropwise to the cyanuric acid solution, and the mixture is heated and stirred for reaction. After the reaction is completed, the mixture is washed with hot water by suction filtration and freeze-dried to obtain a hydrogen-bonded organic framework;
[0007] S2: adding the hydrogen-bonded organic framework to an anhydrous ethanol solution of phenolic resin, stirring the reaction, drying the solid product after centrifugation, and calcining under a protective atmosphere to obtain a carbon absorbing material.
[0008] It is further defined that the mass ratio of melamine to cyanuric acid in S1 is 1.5:(1-2).
[0009] It is further defined that the ethanol concentration in the ethanol aqueous solution in S1 is 40-60 vol%.
[0010] It is further defined that the concentration of the melamine solution in S1 is 0.01-0.02 g / mL.
[0011] It is further defined that the concentration of the cyanuric acid solution in S1 is 0.01-0.02 g / mL.
[0012] It is further defined that the temperature of the heating and stirring reaction in S1 is 70-90° C. and the time is 1-3 h.
[0013] It is further defined that S1 is washed with hot water at 70-90°C.
[0014] It is further defined that the mass ratio of the hydrogen-bonded organic framework to the phenolic resin in S2 is 0.5:(0.3-0.5).
[0015] It is further defined that the concentration of the phenolic resin in the anhydrous ethanol solution of the phenolic resin in S2 is 6-10 mg / mL.
[0016] It is further defined that the reaction in S2 is stirred for 10-12 hours.
[0017] It is further defined that the drying temperature in S2 is 50-70°C.
[0018] The calcination procedure in S2 is further defined as follows: first increase the temperature to 350-450°C at a rate of 1-3°C / min, keep warm for 1-2.5 hours, then increase the temperature to 500-550°C, keep warm for 2-4 hours, continue to increase the temperature to 700-800°C, keep warm for 1.5-4 hours, and cool to room temperature with the furnace after the insulation is completed.
[0019] The second object of the present invention is to provide a one-dimensional tubular carbon absorbing material prepared by the above method, which, when dissolved in deionized water, obtains a one-dimensional tubular carbon absorbing material with a length of 3-5 μm, a tube diameter of 200-400 nm, and a wall thickness of less than 10 nm.
[0020] The third object of the present invention is to provide a three-dimensional network carbon absorbing material prepared by the above method, which, when dissolved in an ethanol aqueous solution, obtains a three-dimensional network carbon absorbing material with a size of 10-40 μm and having micron- and submicron-sized pores.
[0021] A fourth object of the present invention is to provide the above-mentioned one-dimensional tubular carbon absorbing material and three-dimensional mesh carbon absorbing material in a thickness range of 1-5 mm for absorbing electromagnetic waves in a frequency range of 2-18 GHz.
[0022] A fifth object of the present invention is to provide a microwave absorbing coating, wherein the coating is prepared from the above-mentioned one-dimensional tubular carbon microwave absorbing material and the three-dimensional mesh carbon microwave absorbing material.
[0023] Compared with the prior art, the present invention has the following significant effects:
[0024] The present invention provides two morphology-controllable high-performance pure carbon absorbing materials and preparation methods thereof. The method first utilizes hydrogen bonds between melamine and cyanuric acid to drive self-assembly to obtain a hydrogen-bonded organic framework material, and further coats a layer of low-order phenolic resin molecules as a carbon source on its surface through secondary hydrogen bonding. In this process, by changing the liquid phase environment of hydrogen bond self-assembly, the morphology of the prepared hydrogen-bonded organic framework can be effectively regulated. During the heat treatment process, the melamine-cyanuric acid hydrogen-bonded organic framework undergoes a polycondensation reaction, and a carbon nitride phase composed of triazine rings is first generated. As the heat treatment temperature increases, the thermally unstable triazine rings begin to decompose, generating gaseous carbon containing N, part of which overflows from the pores in the inner cavity of the material, and part of which is doped into the carbon matrix derived from the phenolic resin molecules, ultimately forming a unique porous hollow structure. Finally, as the heat treatment temperature continues to increase, the carbon atoms in the carbon matrix undergo partial orderly rearrangement, gradually generating short-range ordered carbon nanocrystals, thereby improving the transmission capacity of electrons. Its innovative points are as follows:
[0025] (1) The present invention drives self-assembly and secondary hydrogen bonding between melamine and cyanuric acid, and realizes controllable adjustment of morphology through simple reaction solvent control. After carbonization, a one-dimensional tubular Mtube and a three-dimensional mesh Mfoam absorbent are constructed. The process is simple and the cost is low.
[0026] (2) The one-dimensional tubular Mtube and three-dimensional mesh Mfoam absorbers prepared by the present invention have a large pore structure, which is conducive to improving the impedance matching characteristics of the material; the order of carbon atoms is low, and there are abundant carbon nanocrystals, N-doped atoms and vacancy defects in between. This structure can effectively control the conductivity of the material within a suitable range while inducing strong polarization relaxation loss. Utilizing the coupling effect between N atom doping, carbon nanocrystal introduction and shape geometry effect, the absorber shows the maximization of the coordination between resistance loss, polarization relaxation behavior and impedance matching, realizing the application requirements of "thin, light, wide and strong".
[0027] (3) The one-dimensional tubular Mtube and three-dimensional mesh Mfoam absorbers prepared by the present invention have excellent electromagnetic wave absorption performance. Thanks to the synergistic effect between multipolarization relaxation behavior, resistance loss and impedance matching, the minimum reflection loss of the two reaches -55.32dB and -26.49 respectively, and the effective absorption bandwidth of ≤-10dB (90% absorption rate) reaches 8.52GHz at a thickness of 2.64mm and 7.88GHz at a thickness of 2.42mm, respectively, covering almost all X and Ku bands. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Scanning electron microscope (SEM) images, high-angle annular dark field scanning transmission electron microscope (HAADF-STEM) images and high-resolution transmission electron microscope (HRTEM) images of the one-dimensional tubular Mtube and three-dimensional mesh Mfoam absorbing materials prepared in Example 1-2; (a) -Mtube-SEM, (c) -Mtube-HAADF-STEM, (b) -Mfoam-SEM, (d) -Mfoam-HAADF-STEM, (e) -Mtube-HRTEM, (f) -Mfoam-HRTEM;
[0029] Figure 2 X-ray diffraction (XRD) patterns and Fourier transform infrared absorption spectra (FTIR) patterns of the one-dimensional tubular Mtube and three-dimensional mesh Mfoam absorbing materials prepared in Example 1-2; (a) -XRD, (b) -FTIR;
[0030] Figure 3 Ultraviolet light-excited Raman spectra (uv-Raman) of the one-dimensional tubular Mtube and three-dimensional mesh Mfoam absorbing materials prepared in Example 1-2;
[0031] Figure 4 The dielectric constant curves of the one-dimensional tubular Mtube and three-dimensional mesh Mfoam absorbing materials prepared in Example 1-2; (a) - real part, (b) - imaginary part;
[0032] Figure 5 The comprehensive absorbing performance of the one-dimensional tubular Mtube and three-dimensional mesh Mfoam absorbing materials prepared in Examples 1-2; (a) - Example 1, (b) - Example 2;
[0033] Figure 6 These are the absorbing performance curves of the one-dimensional tubular Mtube and three-dimensional mesh Mfoam absorbing materials prepared in Examples 1-2 at different thicknesses. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0035] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0036] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.
[0037] The endpoints and any values of the ranges disclosed in the invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.
[0038] Embodiment 1:
[0039] The preparation method of the one-dimensional tubular carbon absorbing material of this embodiment is carried out by the following steps:
[0040] (1) 1.50 g of melamine was added to 100 mL of deionized water, and stirred at 80°C until completely dissolved to obtain a melamine solution. 1.52 g of cyanuric acid was added to 100 mL of deionized water, and stirred at 80°C until completely dissolved to obtain a cyanuric acid solution. The obtained melamine solution was added dropwise to the obtained cyanuric acid solution, and the reaction was stirred at 80°C for 2 h. The product was transferred to a vacuum filtration bottle, washed with 80°C hot water, and freeze-dried for 48 h to obtain a hydrogen-bonded organic framework material.
[0041] (2) 0.5 g of the hydrogen-bonded organic framework product was added to 50 mL of anhydrous ethanol solution of phenolic resin (molecular weight 1000) with a concentration of 0.008 g / mL. The solid product was obtained by centrifugation after stirring for 12 h. The solid product was dried at 60 °C and then placed in a sealed porcelain boat. The solid product was calcined in an argon atmosphere using a tubular furnace. The product was first heated to 400 °C at a rate of 2 °C / min and kept warm for 2 h. The product was then heated to 530 °C at a rate of 1 °C / min and kept warm for 3 h. Finally, the product was heated to 750 °C at a rate of 1 °C / min and kept warm for 3 h. The product was then cooled to room temperature with the furnace and collected to obtain a one-dimensional tubular carbon absorbing material, which was recorded as Mtube.
[0042] Embodiment 2:
[0043] The preparation method of the three-dimensional network carbon absorbing material of this embodiment is carried out according to the following steps:
[0044] (1) Take 1.50 g of melamine and add it to 100 mL of ethanol aqueous solution (deionized water: ethanol, v:v = 1:1), stir at 80°C until it is completely dissolved, and obtain a melamine solution. Take 1.52 g of cyanuric acid and add it to 100 mL of ethanol aqueous solution (deionized water: ethanol, v:v = 1:1), stir at 80°C until it is completely dissolved, and obtain a cyanuric acid solution. The obtained melamine solution is added dropwise to the obtained cyanuric acid solution, and the reaction is stirred at 80°C for 2 hours. The product is transferred to a vacuum filtration bottle, washed with 80°C hot water, and freeze-dried for 48 hours to obtain a hydrogen-bonded organic framework material.
[0045] (2) 0.5 g of the hydrogen-bonded organic framework product was added to 50 mL of anhydrous ethanol solution of phenolic resin (molecular weight 1000) with a concentration of 0.008 g / mL. The solid product was obtained by centrifugation after stirring for 12 h. The solid product was dried at 60 °C and then placed in a sealed porcelain boat. The solid product was calcined in an argon atmosphere using a tubular furnace. The product was first heated to 400 °C at a rate of 2 °C / min and kept warm for 2 h. The product was then heated to 530 °C at a rate of 1 °C / min and kept warm for 3 h. Finally, the product was heated to 750 °C at a rate of 1 °C / min and kept warm for 3 h. The product was then cooled to room temperature with the furnace and the three-dimensional network carbon absorbing material was obtained, which was recorded as Mfoam.
[0046] Test example:
[0047] Take 150 mg of the one-dimensional tubular Mtube prepared in Example 1 and the three-dimensional mesh Mfoam prepared in Example 2, mix them with 3 g PDMS, 0.3 g acetone and 0.3 g curing agent, and place them in a vacuum oven with a vacuum degree of 0.1 MPa for 30 minutes. Take out the mixture and add it to the mold, put it into the vacuum oven again and cure it at 100°C for 1 hour, and finally obtain a coaxial circular ring test sample with an inner diameter of 3.04 mm and an outer diameter of 7.00 mm. Place the prepared coaxial ring in the coaxial transmission line fixture of the vector network analyzer, connect the incident end and the receiving end, and test it in the frequency range of 2-18 GHz.
[0048] Figure 1 a, c are the SEM images and HADDF-STEM images of the one-dimensional tubular Mtube prepared in Example 1. It can be seen from the figures that the length of the one-dimensional tubular Mtube is about 3-5 μm, the tube diameter is about 200-400 nm, and the wall thickness is less than 10 nm.
[0049] Figure 1 b, d are SEM images and HADDF-STEM images of the three-dimensional mesh Mfoam prepared in Example 2. It can be seen from the figure that the size of the three-dimensional mesh Mfoam is tens of microns, and it has many micron-based and submicron-level pores; Figure 1 e and Figure 1 f are HRTEM images of the one-dimensional tubular Mtube prepared in Example 1 and the three-dimensional mesh Mfoam prepared in Example 2, respectively. It can be seen that short-range ordered lattice fringes coexist with the amorphous structure, wherein the lattice fringes correspond to the (002) crystal plane of carbon, and the two exhibit very similar microstructures.
[0050] Figure 2 a is the XRD spectra of the one-dimensional tubular Mtube and the three-dimensional mesh Mfoam obtained in Example 1 and Example 2. The results show that the samples have typical amorphous characteristics. The bun-shaped diffraction peak near 2θ=25° corresponds to the (002) crystal plane of carbon. The broad and diffuse peak shape means that the crystallinity of carbon is low. Figure 2 b is the FTIR spectra of the one-dimensional tubular Mtube and the three-dimensional mesh Mfoam samples obtained in Example 1 and Example 2. The infrared absorption peaks again show that the chemical structures of the two samples are very similar, both containing certain triazine rings and abundant CN groups.
[0051] Figure 3 The uv-Raman spectra of the one-dimensional tubular Mtube and the three-dimensional mesh Mfoam obtained in Example 1 and Example 2 show that both groups of samples have a peak at 1660 cm -1 There is a strong G scattering peak at the position, and no obvious D peak or T peak is observed, indicating that the carbon atoms in them are sp2 Hybrid forms exist. At the same time, compared to the common sp 2 The G peak position of the hybrid carbon material (1585cm -1 ), this phenomenon also indicates that the carbon absorbent prepared by the present invention may contain more olefinic carbon bonds. This is conducive to controlling the conductivity of the absorbent within a suitable range, thereby avoiding an excessively strong skin effect.
[0052] Figure 4 a is the real part of the relative complex dielectric constant of the one-dimensional tubular Mtube and the three-dimensional mesh Mfoam samples obtained in Example 1 and Example 2. It can be seen that the real part of the dielectric constant of the three-dimensional mesh Mfoam is slightly larger than that of the one-dimensional tubular Mtube, and both show strong dispersion phenomenon, but the spectral characteristics of the two curves are very similar, indicating that the change in morphology has no significant effect on the intrinsic electromagnetic response behavior. Figure 4 b is the imaginary part curve of the relative complex dielectric constant. Similarly, the imaginary part of the dielectric constant of the three-dimensional network Mfoam is also slightly larger than that of the one-dimensional tubular Mtube, and the two maintain very similar spectral characteristics. The curve undergoes obvious multiple relaxations at high frequencies, which may be caused by dipole and interface polarization relaxation induced by heteroatom N doping, carbon nanocrystals, and vacancy defects. The above results show that compared with the one-dimensional tubular Mtube, the three-dimensional network Mfoam exhibits stronger dielectric loss capacity, which may be because the three-dimensional network structure is more conducive to the introduction of carrier transmission channels in the insulating matrix.
[0053] Figure 5 a is the comprehensive wave absorbing performance of the one-dimensional tubular sample Mtube obtained in Example 1. It can be seen that within the thickness range of 1-5 mm, the effective absorption bandwidth of the absorber can be adjusted to cover the frequency range of 5-18 GHz. Figure 5 b is the comprehensive absorption performance of the three-dimensional mesh Mfoam sample obtained in Example 2. It can be seen that within the thickness range of 1-5 mm, the effective absorption bandwidth of the absorber can be adjusted to cover the frequency range of 4.5-18 GHz. This shows that the two absorbers have good impedance matching characteristics in a wide bandwidth range.
[0054] Figure 6 The absorption performance curves of the one-dimensional tubular Mtube and the three-dimensional mesh Mfoam obtained in Example 1 and Example 2 reflect the maximum reflection loss and effective absorption bandwidth of each sample. It can be seen that the minimum reflection loss (RL min ) reached -55.32dB; at a thickness of 2.64mm, its ≤-10dB effective absorption bandwidth (EAB) was 8.52GHz; while the RL of the three-dimensional mesh Mfoam was 3.59mm at a matching thickness. minAt a thickness of 2.42mm, its EAB is 7.88GHz. Both show excellent wave absorption performance.
[0055] According to the above graphs and data analysis: The present invention constructs a morphology-controllable pure carbon absorbing material, namely a one-dimensional tubular Mtube and a three-dimensional mesh Mfoam, through a self-assembly-self-sacrificial in-situ carbonization method. The larger pore structure improves the impedance matching characteristics of the material; the carbon atoms in the material have a low degree of order, and there are a large number of carbon olefin bonds, which also contain abundant carbon nanocrystals, N-doped atoms and vacancy defects. This structure can effectively control the conductivity of the material to be within a suitable range while inducing strong polarization relaxation losses. Under the synergistic effect of impedance matching, resistance loss and polarization relaxation loss, the prepared one-dimensional tubular Mtube and three-dimensional mesh Mfoam show excellent absorbing performance, which has good application prospects.
[0056] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a high-performance carbon absorbing material with controllable morphology, characterized in that: The method: S1: Under heating conditions, melamine and cyanuric acid are dissolved in deionized water or ethanol aqueous solution respectively, and then the melamine solution is added dropwise to the cyanuric acid solution, and the mixture is heated and stirred for reaction. After the reaction is completed, the mixture is washed with hot water by suction filtration and freeze-dried to obtain a hydrogen-bonded organic framework; S2: adding the hydrogen-bonded organic framework to an anhydrous ethanol solution of phenolic resin, stirring the reaction, drying the solid product after centrifugation, and calcining under a protective atmosphere to obtain a carbon absorbing material.
2. The method according to claim 1, characterized in that The mass ratio of melamine to cyanuric acid in S1 is 1.5:(1-2), the ethanol concentration in the ethanol aqueous solution is 40-60 vol%, the melamine solution concentration is 0.01-0.02 g / mL, and the cyanuric acid solution concentration is 0.01-0.02 g / mL.
3. The method according to claim 1, characterized in that The temperature of the heating and stirring reaction in S1 is 70-90°C and the time is 1-3h.
4. The method according to claim 1, characterized in that The mass ratio of the hydrogen-bonded organic framework to the phenolic resin in S2 is 0.5:(0.3-0.5), and the concentration of the phenolic resin in the anhydrous ethanol solution of the phenolic resin is 6-10 mg / mL.
5. The method according to claim 1, characterized in that The reaction was stirred in S2 for 10-12 h.
6. The method according to claim 1, characterized in that Calcination procedure in S2: first heat to 350-450°C at a rate of 1-3°C / min, keep warm for 1-2.5h, then heat to 500-550°C, keep warm for 2-4h, continue to heat to 700-800°C, keep warm for 1.5-4h, and cool to room temperature with the furnace after the heat preservation is completed.
7. The one-dimensional tubular carbon absorbing material prepared by the method according to any one of claims 1 to 6, characterized in that: When dissolved in deionized water, a one-dimensional tubular carbon absorbing material is obtained, with a length of 3-5 μm, a tube diameter of 200-400 nm, and a wall thickness of less than 10 nm.
8. The three-dimensional network carbon absorbing material obtained by the method according to any one of claims 1 to 6, characterized in that: When dissolved in ethanol aqueous solution, a three-dimensional network carbon absorbing material is obtained, the size of which is 10-40 μm and has micron-level and submicron-level pores.
9. The absorbing material prepared by the method according to any one of claims 1 to 5 has a thickness in the range of 1 to 5 mm and is used for absorbing electromagnetic waves in the frequency range of 2 to 18 GHz.
10. A microwave absorbing coating, wherein the coating is prepared from the microwave absorbing material prepared by the method according to any one of claims 1 to 5.
Citation Information
Patent Citations
Tubular cobalt-hybridized g-C3N4 material, microwave synthesis method thereof and application of tubular cobalt-hybridized g-C3N4 material in field of supercapacitors
CN114261950A
Preparation method of potassium-oxygen co-doped graphite phase carbon nitride photocatalyst
CN115007182A
Preparation method and application of MOF-derived Co and Zn-doped porous carbon nitride catalyst
CN115090312A
Early-warning flame retardant, preparation method and application thereof, and flame-retardant coating
CN115353764A
Double-layer bead foaming polypropylene wave-absorbing material and preparation method thereof
CN115536941A
Cited By
Graphite crucible and preparation method and application thereof
CN119874408A